Pruning times on the phenology and quality of chardonnay vine (Vitis vinifera L.) - Aloy, Keila; Gobi, Samuel Francisco; Jacobs, Suziane Antes; Eckhardt, Daniel Pazzini; Martins, Hyoran Caius Genindo Barreto; Schumacher, Rafael Lizandro; Brasil Costa, Vagner (Comunicata Scientiae, 2025)
The pruning time can influence the performance of the vine, depending on the local conditions in which it is located. The present study aimed to evaluate the influence of pruning times on the phenology of the Chardonnay vine, on the productivity and quality of the grape and wine in the 2022/2023 production cycle. The experimental design was in randomized blocks, with 3 replications and an experimental unit of 5 plants. The treatments consisted of four pruning times (at the end of May, June, July and August), with assessments of phenology (at the beginning and end of budding, flowering, and maturation), percentage of bud sprouting, production and quality of grapes and wine. Production was evaluated in number of bunches; average weight and size of bunches; productivity per plant and per hectare. The analyzes of must before processing, and wine, were pH; total acidity; sugars, alcohol and volatile acidity. Early pruning (T1) reduces the duration of phenological cycles. Early pruning resulted in lower production. The must from control (3) presented the highest value for total acidity. T1 did not change the duration of the phenological subperiods nor did it bring forward the harvest, in relation to the control. However, it may increase the risk of damage to shoots due to late frosts, in years with winter temperatures close to 0 °C. The different pruning times influenced the productivity and not the composition of the grapes. It is possible to extend the pruning period and stagger the workforce to carry out dry pruning.